2006
DOI: 10.1016/j.cub.2005.11.033
|View full text |Cite
|
Sign up to set email alerts
|

Ken & Barbie Selectively Regulates the Expression of a Subset of JAK/STAT Pathway Target Genes

Abstract: A limited number of evolutionarily conserved signal transduction pathways are repeatedly reused during development to regulate a wide range of processes. Here we describe a new negative regulator of JAK/STAT signaling and identify a potential mechanism by which the pleiotropy of responses resulting from pathway activation is generated in vivo. As part of a genetic interaction screen, we have identified Ken & Barbie (Ken) , which is an ortholog of the mammalian proto-oncogene BCL6 , as a negative regulator of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 39 publications
1
56
1
Order By: Relevance
“…A role for Ken & Barbie (KEN) in the selective regulation of STAT92E activity has also recently been demonstrated, a finding that could advance our understanding of how a single pathway can mediate diverse developmental processes (Arbouzova et al, 2006). KEN is the Drosophila homologue of human BCL6 (B-cell lymphoma 6) and belongs to the family of BTB/POZ domaincontaining transcriptional repressors (Fig.…”
Section: Ken and Barbie/bcl6mentioning
confidence: 97%
“…A role for Ken & Barbie (KEN) in the selective regulation of STAT92E activity has also recently been demonstrated, a finding that could advance our understanding of how a single pathway can mediate diverse developmental processes (Arbouzova et al, 2006). KEN is the Drosophila homologue of human BCL6 (B-cell lymphoma 6) and belongs to the family of BTB/POZ domaincontaining transcriptional repressors (Fig.…”
Section: Ken and Barbie/bcl6mentioning
confidence: 97%
“…Specifically, those STAT92E-binding sites containing a GAAA (i.e. an additional A in their final position) are recognised and repressed by Ken, so down-regulating a specific subset of pathway target genes at multiple stages of development [13]. More recently, Kwon et al have revealed a potential mechanism for Ken-mediated transcriptional repression [14 ].…”
Section: Mining For New Jak/stat Regulatorsmentioning
confidence: 98%
“…by inappropriate JAK/STAT pathway activation. The first of these, using ectopic Upd expression in the eye as its assay identified a number of genes, including the histone variant, His2A.V and the ken and barbie (ken) locus [12,13] ( Table 1). ken encodes a site-specific transcriptional repressor that binds to a DNA site made up of an essential core sequence present within the palindromic nTTCnnnGAAn sites recognised by STAT92E.…”
Section: Mining For New Jak/stat Regulatorsmentioning
confidence: 99%
“…STAT then activates a downstream pathway. Ken, a DNA binding protein is among the different downstream targets of the JAK-STAT pathway [45]. Interestingly, we have recently demonstrated that Ken is involved in the control of Drosophila telomeres by regulating the expression of the TART retrotransposon through specific binding sites [17].…”
Section: Discussionmentioning
confidence: 99%